A formação do professor de artes na rede estadual de ensino em três cidades da Região do Bico do Papagaio-to: um estudo exploratório. - Almeida, Ludimila Silva (Universidade Federal do Tocantins, 2019)
Thus, we show that art has been through difficult times in recent years, since it is the margin of other disciplines, being considered more as a curricular activity, nor an important curricular discipline and area of knowledge, since the system is more concerned with reading and writing (not that they are less important) and thus leaves aside the teaching of the arts, since it is fundamental for the student in what concerns creativity, imagination, motor coordination, visual readings, senses, musical perception and also we can not fail to include social and cultural interaction. It presents as main objective to analyze the profile of the teachers who teach the discipline of Art in the state schools of the municipalities of Araguatins, Augustinópolis and Esperantina, in the Bico do Papagaio region, Tocantins. As methodology, this research follows the perspective of the qualitative approach, of documentary, bibliographic and empirical characteristics. In accordance with this methodology, we also used the semi-structured questionnaire applied to teachers who work in the Art discipline in these three cities, seeking to understand their profile and raise questions about the problem of this research. Among some results, we found from the results found that after going to the teaching units surveyed, that the teachers participating in the questionnaire proposed by the study, besides not being trained in this area, presented inadequate methodologies to develop the teaching potential and learning in the arts, since the expositive and explanatory classes were predominant as the most common means of "passing on" the contents that need to be studied in this area, according to their reports. This research also proved what was once only personal assumption: that art teaching is performed by people from other areas in the Bico do Papagaio region. With this, I noticed a lack of initial and continuing training courses for the arts (visual arts, theater, dance and music) that can meet the demand of teachers trained in this area for the state public network of the region researched, which would fill the gap in that territory. :